Enhancing Student Writing Skills About Conditional Sentenses Through Media and ICT in ELT - Sihombing, Santa R.; Simbolon, Selina; Pakpahan, Rotua; Herman, Herman (Universitas Ibn Khaldun, 2025)
This initiative was developed to strengthen the listening abilities of by introducing them to the English Skills TOEFL Test. Seminari Menengah Sacerdoces Pematangsiantar The program was initiated in response to the rising importance of English language proficiency, particularly in English skills, which is vital for academic growth and competitiveness in international contexts. Many students lacked prior knowledge of the English Skills TOEFL Test and had minimal access to learning tools and guidance, revealing a need for improved language support and exposure.The approach used in this program was based on a socialization framework and involved three main stages: planning, execution, and assessment. Data were collected through direct observation and field notes during the session, which was held on June 6, 2025, with 20 student participants. The implementation phase featured lectures supported by PowerPoint presentations that explained the test's definition, structure, benefits, and strategies. These were followed by interactive discussions and Q&A sessions. Students were also introduced to free online practice resources and information about available TOEFL test centers.The outcomes demonstrated that students gained new insights into the TOEFL test, participated actively in the sessions, and showed increased understanding of the role of English proficiency in their future educational and career paths. Although some challenges were noted, such as limited background knowledge and low initial interest, these were effectively addressed through engaging materials and collaborative support from teachers.In summary, the program successfully provided essential knowledge about the English Skills TOEFL Test and contributed to the development of students’ listening skills, helping to prepare them for academic success and wider global opportunities.